THE EFFECT OF 20% Saccharomyces spp. FERMENTED TOFU WASTE IN RATION TO CARCASS WEIGHT AND PHYSICAL CARCASS COMPOSITION OF BROILER CHICKEN - G. A. P., Juliani; Bidura, I G. N. G.; Utami, I. A. P. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
This study has been carried out to investigate the effect of utilization 20% tofu waste fermented by Saccharomyces spp. on ration to physical carcass composition of broiler chicken. Complete Randomized Design (CRD) with three treatments and six replicates was used in this study. Those three treatments were basal ration without tofu waste as control (A), ration containing 20% tofu waste (B), and the ration containing 20% tofu waste fermented (C). Variables observed carcass weight and it’s physical composition were meat, bone and subcutaneous fat including the skin carcass. The result showed that fed ration containing 20% tofu waste fermented by Saccharomyces spp. (treatment C) increasing (P<0.05) carcass weight and meat carcass percentage and decreasing (P<0.05) subcutaneous fat including the skin carcass percentage compared fed ration without tofu waste (treatment A). Adding 20% tofu waste on ration (treatments B) so increasing (P<0.05) meat carcass percentage and decreasing (P<0.05) subcutaneous fat including the skin carcass percentage broiler. Meanwhile on bone carcass percentage all treatments has not significant defferent (P>0.05). It was concluded that utilization 20% tofu waste fermented by Saccharomyces spp. on ration can increasing carcass weight and meat carcass percentage and decreasing subcutaneous fat including the skin carcass broiler. Keyword: Tofu waste, Saccharomyces spp., Carcass, Carcass physical compositon, Broiler.